Fertility preservation in pig using ovarian tissues by vitrification method - In-Sul Hwang (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Cryopreservation of porcine ovarian tissue by vitrification method is a promising approach to preserve genetic materials for future use. However, information is not enough and technology still remains in a challenge stage in pig. Therefore, the objective of present study was to determine possibility of vitrification method to cryopreserve porcine ovarian tissue and to confirm an occurrence of cryoinjuries. Briefly, cryoinjuries and apoptosis patterns in vitrified-warmed ovarian tissue were examined by histological evaluation and TUNEL assay respectively. In results, a damaged morphology of oocytes was detected among groups and the rate was significantly (p< 0.05) lower in vitrification group (25.8%) than freezing control group (67.7%), while fresh control group (6.6%) showed significantly (p< 0.05) lower than both groups. In addition, cryoinjury that form a wave pattern of tissues around follicles was found in the frozen control group, but not in the fresh control group as well as in the vitrification group. Apoptotic cells in follicle was observed only in freezing control group while no apoptotic cell was found in both fresh control and vitrification. Similarly, apoptotic patterns of tissues not in follicle were comparable between fresh control and vitrification groups while freezing control group showed increased tendency. Conclusively, it was confirmed that vitrification method has a prevention effect against cryoinjury and this method could be an alternative approach for cryopreservation of genetic material in pigs. Further study is needed to examine the viability of oocytes derived from vitrified-warmed ovarian tissue.